Perancangan Agrowisata Kopi Dengan Pendekatan Desain Berkelanjutan Di Desa Pujungan, Pupuan, Tabanan, Bali - I Made Riandika Surya Wiguna; Ni Wayan Meidayanti Mustika; I Wayan Runa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Pupuan district which is the second rank of the most robusta coffee production in Bali with a total production of 2,663.0. In addition to the area of land and coffee production in the Pujungan area, this area also has tourist potential. The potential possessed by this village has not been utilized and developed properly because of the lack of facilities that are able to accommodate the process of cultivation, research, coffee processing, and low public awareness about the potential of the area itself. The methods used in data collection are surveying, literature studies, and observation, as well as data compilation and classification methods used for the presentation of data. Then the data obtained is analyzed by comparative methods, analysis, reduction, and synthesis. Coffee Agrotourism is designed to accommodate various main facilities that are channeled through the potential in Pujungan Village, such as educational facilities about the history and cultivation of coffee in Pujungan Village, how to grow coffee directly, traditional and modern coffee processing. The green architecture design with the concept of Sustainable Agritourism design is chosen because it is based on principles that aim to align the building with the surrounding environment and is oriented to long-term aspects, and the design of the development of coffee plantations remains sustainable in various aspects.